Access to Justice in the Republic of Kazakhstan and the Status Quo AI - Sidorova, N.V.; Serikbayev, A.M. (Bulletin of the Karaganda University “Law Series”, 2025)
The purpose of this study is to analyze the population’s access to justice in the Republic of Kazakhstan, identify current problems and determine the prospects for eliminating barriers and risks in access to justice through the use of artificial intelligence tools. As a result of the study, the authors came to the conclusion that in the context of digital transformation, the main trajectory of justice development in Kazakhstan is Legal tech, in the structure of which a new track of innovative modernization has been formed — Legal AI. These technological solutions are a tool for expanding the population’s access to justice in Kazakhstan, which were formed during the period of digitalization of the judicial system, but at the present stage, the possibilities of using artificial intelligence in solving problems of access to justice, as well as in the future of predictive justice, have been updated. The main results of the study are that the authors formulated conclusions about the level of access of the population to justice in modern conditions, identified factors that impede the implementation of the right to equal access to justice, proposed directions for improving the digital accessibility of justice, including the introduction of artificial intelligence tools. The main conclusion based on the results of the study is the justification for the formation of a new digital platform, which will unify and systematize auxiliary services for legal support of the population, allowing to independently build a trajectory (algorithm) of participation in the trial, minimize time and financial costs, predict the outcome of the case and solve the problem of financing legal costs. The proposed digital platform is a new tool for ensuring access to justice, operating on the basis of artificial intelligence algorithms.